Is bullying in the eye of the beholder? : Examining employees' perceptions of workplace bullying in the education and hospitality sectors : a thesis presented in partial fulfilment of the requirements for the degree of Master of Management in Management at Massey University, Albany campus, New Zealand - Alhaseny, Sokaina (Massey University, 2014)
The literature suggests that dominant behavioural and attitudinal norms within an industry may influence an employee’s perception of what constitutes workplace bullying. The present study investigated this possibility by collecting data in relation to perceptions of workplace bullying from employees in Education (an industry with a potentially low tolerance for workplace bullying) and in Hospitality (an industry with a potentially high tolerance for workplace bullying). Semi-structured, in-depth interviews were conducted with a representative sample of 16 full-time secondary school teachers and 16 full-time bar workers. Firstly, participants were required to read and respond (with the help of prompt questions) to three short, purpose-written scenarios. One scenario described a bullying situation, one a performance management situation and one a one-off harassment episode. These scenarios were used as prompts to get participants thinking and talking about specific behaviours in the workplace. Until this point in the interview, there was no mention of ‘workplace bullying’. Part two of the interview explored how participants defined workplace bullying and what criteria they used. As part of this process, participants were asked to reflect back to the three scenarios and say which, if any, described workplace bullying. The content of the interviews was transcribed and analysed using thematic analysis. Although there were similarities between the two sectors in respect of employees’ perspectives of workplace bullying, there were also substantial differences. Participants from both industries believed that people in authoritative positions were most likely to be causing or fuelling bullying, and certain personality traits (e.g. introversion) made individuals more prone to being targeted. In relation to industry differences, the participants from the Hospitality sector often seemed to find it difficult to distinguish between bullying and what they saw as ‘harmless joking around’, whereas the participants in the Education sector tended to have an understanding of bullying which was more in line with the academic literature. Both groups appeared to have very different norms associated with how new employees were treated. In Hospitality the perception was that newcomers were purposely picked on, for the sole reason that they are new (bullying is– or should be – accepted by new people as part of ‘fitting in’), whereas, newcomers to the Education sector tend to be actively looked after and given more time to fit in. The differences presented in this study highlight the importance of understanding the conceptualisation of bullying in different workplace environments. The study gives an insight into how industry norms can potentially be related to employee perspectives. These differences and norms could be the underlying reason why bullying is still prevalent. This research could potentially be a step towards prevention initiatives for improving and creating a healthier work environment. It may raise the awareness of policymakers and cause them to consider the conceptual differences among industries. This research may also influence the prevention of bullying through the use of customised initiatives that inform employees about what is and is not acceptable behaviour (irrespective of industry).
Keywords: Workplace bullying; Perceptions of bullying; Education sector bullying; Hospitality sector bullying